Arterial Tortuosity and Its Correlation with White Matter Hyperintensities in Acute Ischemic Stroke - Ke Shang; Xiao Chen; Chang Cheng; Xiang Luo; Shabei Xu; Wei Wang; Chenchen Liu (Neural Plasticity)
Introduction. The association between arterial tortuosity and acute ischemic stroke (AIS) has been reported, but showing inconsistent results. We hypothesized that tortuosity of extra- and intracranial large arteries might be higher in AIS patients. Furthermore, we explored the correlation between artery tortuosity and white matter hyperintensity (WMH) severity in AIS patients. Methods. 166 AIS patients identified as large artery atherosclerosis, and 83 control subjects were enrolled. All subjects received three-dimensional computed tomography angiography (CTA). Arterial tortuosity was evaluated using the tortuosity index. WMHs were evaluated using magnetic resonance imaging in all AIS patients. Results. AIS patients showed significantly increased arterial tortuosity index relative to controls, including left carotid artery (CA) (p=0.001), right CA (p<0.001), left common carotid artery (CCA) (p<0.001), right CCA (p<0.001), left internal carotid artery (p=0.001), right internal carotid artery (p=0.01), left extracranial internal carotid artery (EICA) (p<0.001), right EICA (p=0.01), and vertebral artery dominance (VAD) (p=0.001). The tortuosity of all above arteries was associated with the presence of AIS. AIS patients with moderate or severe WMHs had a higher tortuosity index in left CA (p=0.005), left CCA (p=0.003), left EICA (p=0.07), and VAD (p=0.001). In addition, the tortuosity of left EICA and VAD was associated with WMH severity in AIS patients. Conclusions. Increased extra- and intracranial large arteries tortuosity is associated with AIS. The tortuosity of left carotid artery system and vertebral artery may be the independent risk factors for WMH severity in AIS patients. Clinical Trial Registration. This trial is registered with NCT03122002 (http://www.clinicaltrials.gov).